Motivation solusion for laborers at Hai Ha Kotobuki Limited liability Company = Giải pháp tạo động lực cho lao động trực tiếp tại công ty TNHH Hải Hà - Kotobuki. Luận văn ThS. Kinh doanh: 60 34 01 - Nguyễn, Thị Lan (2019)
Chapter 1: AN OVERVIEW OF RESEARCH. Chapter 2: SOME BASIC THEORIES ON EMPLOYEE MOTIVATION . Chapter 3: EMPLOYEE MOTIVATION IN HAI HA- KOTOBUKI LIMITED COMPANY. Chapter 4: SOME SOLUTIONS TO IMPROVE DIRECT EMPLOYEE MOTIVATION IN HAI HA – KOTOBUKI LIMITED COMPANY .